2007
DOI: 10.1142/s1793292007000519
|View full text |Cite
|
Sign up to set email alerts
|

Continuum Modeling of Interfaces in Polymer Matrix Composites Reinforced by Carbon Nanotubes

Abstract: The interface behavior may significantly influence the mechanical properties of carbon nanotube (CNT)-reinforced composites due to the large interface area per unit volume at the composite. The modeling of CNT/polymer interfaces has been a challenge in the continuum modeling of CNTreinforced composites. This paper presents a review of recent progress to model the CNT/matrix interfaces via a cohesive law established from the van der Waals force. A simple, analytical cohesive law is obtained from the interatomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…It is evident that the interfacial normal cohesive stress of the interface between the Gr and Al (111) is the highest. The curves can be divided into two stages [40]. First, the cohesion of the interface rises rapidly and reaches its peak with the increase of displacement.…”
Section: Resultsmentioning
confidence: 99%
“…It is evident that the interfacial normal cohesive stress of the interface between the Gr and Al (111) is the highest. The curves can be divided into two stages [40]. First, the cohesion of the interface rises rapidly and reaches its peak with the increase of displacement.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 The addressable nanowires were grown in micron or sub-micron width and several micrometer lengths between pre-deposited gold electrodes with various materials like metals and conducting polymers. [9][10][11] This fabrication method is highly controllable, addressable, efficient, and attractive for large-scale integrated system with various materials that are possibly electrochemically deposited. While it has several benefits to overcome the drawbacks from other typical methods, it may cause unexpected dendrite or sparse structures in grown nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome the nanoscale experimental limitations, a significant amount of modeling research has been reported to study the molecular scale properties of composites using ab-initio quantum chemistry, density functional theory (DFT), and molecular dynamics (MD) methods [23][24][25][26][27][28][29][30]. MD generated properties of graphene nanoplatelets in epoxy were integrated within a multiscale model using GMC micromechanics by Hadden et al [23].…”
Section: Introductionmentioning
confidence: 99%
“…MD generated properties of graphene nanoplatelets in epoxy were integrated within a multiscale model using GMC micromechanics by Hadden et al [23]. Jiang et al [24,25] modeled the macroscopic behavior of CNT-reinforced nanocomposites using a form of the rule of mixtures. In their work, the interphase between the polymer matrix and a CNT is modeled as a wavy surface and a cohesive stress law is formulated based on the Lennard-Jones potential.…”
Section: Introductionmentioning
confidence: 99%